2012
DOI: 10.1007/s10566-011-9168-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Culturally Adapted Strengthening Families Program 12–16 Years for High-Risk Irish Families

Abstract: Background Evidence-based programs (EBPs) targeting effective family skills are the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
1
38
0
13
Order By: Relevance
“…Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors. These positive results have been reported in different settings (Aalborg et al, 2010;Letarte, Normandeau & Allard, 2010;Redmond et al, 2009;Henggeler & Schoenwald, 2011;Brook, McDonald & Yan, 2012;Donavan, Wood, Frayjo, Black & Surette, 2012), target groups (Mindel & Hoefer, 2006;Orte, Touza, Ballester & March, 2008;McDaniel, Braiden, Onyekwelu, Murphy & Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, & Matthys, 2012;Kumpfer, Whiteside, Greene & Allen, 2010), cultures (Skärstrand, Larsson & Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie & O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina & Ciairano, 2012) and addicted behaviours (Trudeau, Spoth, Randall & Azevedo, 2007;Zhong, et al, 2011;Donovan et al, 2012). …”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 73%
“…Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors. These positive results have been reported in different settings (Aalborg et al, 2010;Letarte, Normandeau & Allard, 2010;Redmond et al, 2009;Henggeler & Schoenwald, 2011;Brook, McDonald & Yan, 2012;Donavan, Wood, Frayjo, Black & Surette, 2012), target groups (Mindel & Hoefer, 2006;Orte, Touza, Ballester & March, 2008;McDaniel, Braiden, Onyekwelu, Murphy & Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, & Matthys, 2012;Kumpfer, Whiteside, Greene & Allen, 2010), cultures (Skärstrand, Larsson & Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie & O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina & Ciairano, 2012) and addicted behaviours (Trudeau, Spoth, Randall & Azevedo, 2007;Zhong, et al, 2011;Donovan et al, 2012). …”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 73%
“…This was completed by the young person (other family members were not asked to complete this instrument). This measure has been used previously in similar populations 88,89 and has undergone extensive development and validation work. It has shown acceptable levels of internal consistency in a validation study with 1298 pupils aged 11-18 years from 16 schools in Victoria, Australia (Cronbach's alpha of 0.39 for the expressiveness scale, 0.67 for the cohesion scale and 0.72 for the conflict scale), 90 test-retest reliability of each subscale of at least 0.73 and good content and construct validity.…”
Section: Important People Drug and Alcohol Interviewmentioning
confidence: 99%
“…• The Strengthening Families Program (SFP), originally a selective family-based program first developed in 1983 in Utah in the USA (Kumpfer et al 2012), was revised in 1992 into a shorter (and more universal) version (Molgaard et al 2000), the Iowa SFP. Versions of the SFP are currently being implemented in Germany, Ireland, Greece, Spain, the Netherlands, Austria, Poland, Portugal, Slovenia, Sweden, and the UK.…”
Section: Examples Of Successful Transfermentioning
confidence: 99%